Expanding clinical characteristics and genotypic profiling of Yao syndrome in Chinese patients - Zhang, Jingyuan; Huang, Xin; Shen, Min (Frontiers in Immunology, 2024)
Objectives: Yao syndrome (YAOS, OMIM# 617321) is a kind of systemic autoinflammatory diseases (SAIDs) linked to the nucleotide-binding oligomerization domain containing 2 (NOD2). Clinical reports of YAOS in China are sparse. Herein, we reported the largest YAOS cohort of Chinese patients to expand the understanding of its phenotype, genotype, and therapeutic responses. Methods:This study enrolled 15 adult patients diagnosed with YAOS at Peking Union Medical College Hospital from April 2015 to May 2024. Whole-exome sequencing was performed on all patients. Clinical data, genetic variations, and treatment responses were documented and compared with a Caucasian cohort. Results:The mean age of disease onset was 35±17 years old. The most common clinical manifestations included recurrent high-grade fever (100%), gastrointestinal symptoms (73.3%), arthralgia/arthritis, fatigue, myalgia, and lower extremity swelling (46.7%). All patients exhibited elevated acute-phase reactants during episodes. 12 heterozygous NOD2 variants were identified, with Q902K in 4 patients, R471C in 3, and variants c.-14C>T, A110T, S127L, R311W, A432V, Y514H, R541P, A661P, K818Q, A886V each found in individual patients. 90% of the patients responded well to glucocorticoids, and 55.6% to sulfasalazine. 66.7% of patients who received TNF inhibitors achieved complete resolution of symptoms. Additionally, one patient each responded favorably to canakinumab and tocilizumab. Compared to the Caucasian cohort, our cohort exhibited a more balanced gender ratio and a higher proportion of recurrent fever, proteinuria/hematuria as well as more frequent leukocytosis, elevated acute phase reactants, and anemia. Lower proportions of arthralgia/arthritis, skin rashes, headaches, and sicca-like symptoms were noted in our cohort. Moreover, a higher proportion of patients in our cohort showed a good response to TNF inhibitors. Conclusions:Chinese patients with YAOS had more pronounced inflammatory manifestations compared to the Caucasian cohort. Variants c.-14C>T, A110T, S127L, A661P, K818Q, A886V, R471C, and A432V were identified as novel NOD2 variants in YAOS. TNF, IL-6, and IL-1 inhibitors are the promising treatment options. These findings expand the clinical spectrum, genetic profile, and treatment efficacy of YAOS, underscoring the need for heightened awareness of this disease in diverse populations.